Variação Linguística: o enfoque dos livros didáticos de língua portuguesa da educação de jovens e adultos - Ires Figueredo de Souza (2019)
This research aims to investigate how the linguistic variation is approached in the Portuguese language textbooks of Elementary School II of the young and adults education (EJA). The treatment of linguistic variation in the school context is a challenge for the teacher. There is a need to constantly rethink pedagogical practices that involve this issue, even more in the case of EJA, a modality in which educational practices are even more complex. The scientific relevance of this study lies in the need to understand how the textbook deals with linguistic variation. Some questions have triggered this study, such as: How is linguistic variation treated in the textbooks of Elementary School II of EJA? Does the textbook address the concept of "right" and "wrong"? Does the book deal with linguistic discrimination? Therefore, this research aims to contribute to the construction of knowledge about textbooks and, especially, how they deal with questions related to the teaching of linguistic variation. The theoretical framework used in this research is based on the sociolinguistics and educational sociolinguistics studies (BORTONI-RICARDO, 2004; BAGNO, 2007), which point out the need to consider the social relations in linguisticas change and variation in mother language teaching. In order to investigate this matter, two book collections approved by the PNLD-EJA (2014) were selected, and, as a methodology, we used documentary analysis and bibliographic research in the frame of the qualitative/interpretative approach. The data analysis showed that there are few activities presented that deal specifically with linguistic variation. In most cases, the variation appears secondarily. We also observed that the lexical variation is prioritized in both collections and there is, in fact, no specific and systematic work on the many types of variations as well as on stigma and linguistic discrimination. We hope that this work will allow a reflection on the textbooks of Elementary School II and will also encourage more studies that promote a deeper understanding about the linguistic variation.